Genetic experience: assessment and credence of the DNA test in criminology and criminal process - Flores Clavo, Rene (2021)
Over the years, the procedures for the extraction of DNA fingerprints have become more and more uniform and detailed in terms of obtaining them, being that this type of evidence has been chosen as one of the main ones within the criminal process, displacing the testimonial evidence.However, it is important to verify if the current legislation has been advancing according to the steps of science and, above all, to analyze questions about its reliability to prove certain criminal acts.This is a descriptive bibliographic review of qualitative character where we will try to make evident the importance of DNA evidence and forensic genetics in criminal proceedings. Science is advancing more and more and so are the techniques used in the analysis of DNA evidence, thus incorporating specialized methodologies in the investigation of crimes. Courts have recognized that DNA evidence can be more reliable than eyewitnesses, therefore, all these advances make review articles necessary and important so that we can have a more accurate assessment of what is presented in a genetic expertise.